Karakteristik Mikoriza Arbuskula Tanaman Serai Wangi (Cymbopogon nardus L.) di Lapangan Ternaungi dan Tidak Ternaungi - Nampiah Sukarno; Rahayu Laelandi; Ibnu Qayim; Mega Putri Amelya (Jurnal Ilmu Pertanian Indonesia, 2022)
Arbuscular mycorrhiza (AM) characteristics of citronella grass in the field have not been reported. This research aimed to study the AM characteristics of citronella grass grown in unshaded and shaded fields. The roots of citronella grass were collected from citronella grass plantations in Cianjur, West Java. The root samples were analyzed for AM structures, namely entry points, intercellular hyphae, arbuscules, and vesicles. The results showed that the citronella grass form AM colonization. The quality of root colonization differed between the two cultivation systems. The unshaded citronella grass had higher root colonization compared to shaded citronella grass. In the unshaded citronella grass, the number of arbuscules was 7 per cm of root length, whereas in the shaded citronella grass was 4 per cm of root length. The types of arbuscules observed were arum and intermediate. There were no differences in the number of entry points in the two cultivated systems, which was 3,5 entry points per cm of root length. The numbers of vesicles and internal hyphae in unshaded citronella grass were lower than that of in the shaded citronella grass. In the unshaded citronella grass, the number of vesicles and intracellular hyphae were 1,5 and 8,5 per cm root length, whereas in the shaded citronella grass were 3,5 and 11 per cm root length, respectively. Shading plants grown in the field were bamboo, banana, coffee, tea, and sugar palm. All the shading plants formed AM symbiosis with a colonization value of 7 to 30%. This research indicates that arbuscular mycorrhiza is an important component in the citronella grass cultivation in unshaded and shaded fields. Keywords: Arbuscule, entry point, intercellular hyphae, root colonization, vesicle